2020
DOI: 10.1016/j.jsxm.2020.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Severity of Coronary Artery Disease and Aorto-Ilio-Pudendal Artery Disease in Patients with Ischemic Heart Disease–Associated Vascular Erectile Dysfunction

Abstract: Background The angiographically documented association between severity of coronary artery disease (CAD) and aorto-ilio-pudendal (A-I-P) artery disease and vascular erectile dysfunction (ED) was not yet settled. Aim To assess the relation between angiographically proved CAD and A-I-P artery disease in patients with ischemic heart disease (IHD)–associated vascular ED. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Our results showed that the degree of coronary artery stenosis correlates with the degree of II-IPA stenosis, which agrees with the findings of Rogers et al [18] and Sanad et al [19]. We believe that these findings confirm the reasonable assumption that there is a correlation between coronary artery stenosis and II-IPA stenosis because CAD and ED are linked to the common pathophysiology of vascular endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results showed that the degree of coronary artery stenosis correlates with the degree of II-IPA stenosis, which agrees with the findings of Rogers et al [18] and Sanad et al [19]. We believe that these findings confirm the reasonable assumption that there is a correlation between coronary artery stenosis and II-IPA stenosis because CAD and ED are linked to the common pathophysiology of vascular endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…Rogers et al [18] performed CAG and PA in 10 patients with suspected CAD and ED who were nonresponsive to phosphodiesterase-5 inhibitor (PDE5i) and reported a correlation between CAD and IPA disease in patients with ED. Sanad et al [19] performed CAG and PA to examine the relationship between angiographically verified CAD and aorto-ilio-pudendal (A-I-P) artery disease in patients with ischemic heart disease-associated vascular ED (n = 60). They reported that ED correlates with A-I-P vascular lesions than with CAD alone, and that there was a significant association between the severity of CAD and A-I-P artery disease in patients with CAD associated with ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing amount of evidence that IHD has high co-existing morbidity burden, previous studies investigating IHD comorbidity have been predominately focused on a few common diseases and interpreted them using prevalence statistics and correlation analysis [ 7 , 9 , 10 , 12 , 13 ], without a comprehensive investigation of associations between comorbidities in patients with IHD, and most of these studies were conducted in Western countries [ 15 , 16 , 17 , 18 ]. There is still a significant gap in knowledge regarding the comorbidity patterns of IHD, especially among Chinese individuals, who tend to exhibit different lifestyles and eating habits from those observed in Western countries.…”
Section: Introductionmentioning
confidence: 99%